Shake off those caterpillars - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
If you notice Helicoverpa caterpillars in your field of pigeon peas, call over a couple of friends or family members and start shaking the vermin from the plants. Shaking and collecting them on plastic sheets laid out between the rows of plants and...